The Role of School Leadership in the Success of Literacy Programs - Lina Suryati; Urip Sulistiyo; Sofyan; Mirnawati (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
In an effort to foster a reading culture, the Indonesian government has launched various initiatives to improve literacy, particularly among the younger generation. Schools, as formal educational institutions, play a strategic role in shaping students' intellectual and moral development. In this context, school principals hold a central role as leaders—not only in promoting literacy culture but also in instilling Islamic values such as honesty, responsibility, and the pursuit of knowledge as a form of worship. This study aims to examine the role of school leadership in enhancing the literacy culture at SMP Negeri 21 Batang Hari. A descriptive qualitative method was used, with data collected through interviews, observations, and documentation involving principals, teachers, the head librarian, and students. Data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the principal plays a key role in mobilizing, guiding, motivating, and setting an example in fostering literacy at school. Islamic values are integrated into activities such as reading as a form of reflection (tadabbur), building unity (ukhuwah) through shared reading sessions, and modeling appropriate reading manners (adab). The study concludes that effective, inspirational leadership rooted in Islamic values is essential in creating a school environment that holistically and meaningfully supports the development of a literacy culture.